Pkm Rancangan, Pelaksanaan, Dan Laporan Penelitian Tindakan Kelas Bagi Guru Smp/Mts Di Kabupaten Barru - Sirajuddin Saleh; Supriadi Torro; Dimas Ario Sumilih; Sulmiah Sulmiah (Panrita Inovasi: Jurnal Pengabdian Kepada Masyarakat, 2024)
The main problem faced by the partners is not yet a good understanding of the concept of action research (CAR), the Partners can not distinguish between types of classroom action research with other research, and partners do not understand the procedures for the preparation of classroom action research report. Therefore, in order to overcome the problems mentioned above, the proposed solution is to conduct training and guidance to partners on research, class actions, particularly in the preparation of classroom action research report. The training is expected to produce a systematic format of writing / preparation of reports Classroom Action Research (CAR), and teachers who have been trained (partners) have the skills / understanding in preparing classroom action research report.